PENGGUNAAN GERGAJI RANTAI PADA PENEBANGAN JATI DAN DAMPAKNYA TERHADAP KEBISINGAN DAN BEBAN KERJA - Soenarno Soenarno; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1991)
It is  obvious that  the use. of  chainsaw in teak felling has some advantages not only in increasing productivity but also in reducing felling defects.Nevertheless, uaing chainsaw in teak felling has also created a lot of inconveniences  to forest worker. Thess inclu de the distruction of physical climatic conditions and heavier phsycological stress  of forest  workers due to combined physical workload, noise and fear of accident effects.Base on the above reasons research on noise and  forest workers' workstress. is needed. this research is intended to determine a better method of felling technique in the efforts  of controlling noise to provide a more favourable conditions for  the workers. This research was  carried  out in Saradan Forest District, East Java.The  results  of the research reveal that both noise and the  workers' streu  rate occurinf at teak felling ia higher than at acceptable by  the  "World medical conventiont"  (Grandjean, 1982). The avercwe noise level rate it about 110 dB(A), and the average forest workers' streu  is about  126  heart beats/min for chainsaW operator and about 98 heart beats/min for   the helper.